Empowering Communities for Environmental Change: Waste Segregation Solutions in Alido Heights - Beltran, Ian Hendrix G.; Estrella, John Moses Z.; Masaba, Jolina G.; Punzal, Stevince S.; Tongga, Raizza P. (Three E Science Institute, 2023)
One of the significant environmental challenges we face is improper waste segregation. Poor waste disposal practices hinder the progress of integrated solid waste management in households. This study aims to identify problems encountered during implementation and provide specific solutions to enhance the quality of life for residents and the Homeowners Association and establish adequate waste segregation practices that promote environmental cleanliness. The study utilizes quantitative and qualitative methods with a descriptive design to evaluate the waste segregation system in Alido Heights Subdivision, Bulihan, City of Malolos, Bulacan. The researchers designed a survey questionnaire with questions constructed and developed based on the issues identified by the residents. Simultaneously, interviews were conducted with an officer of the homeowners’ association to gather their knowledge and experiences. The results indicate that the respondents effectively manage household waste and segregation. Furthermore, the efficiency of the waste segregation system implemented by the subdivision reveals inadequacies in designated waste disposal equipment and the location of the dumping site, resulting in inefficient waste segregation within the subdivision. The improvement programs recommended by the subdivision’s residents include providing more garbage bins, allocating additional waste disposal sites, and implementing a campaign program to establish a more efficient segregation system among the residents in the area.